2022
DOI: 10.3389/fonc.2022.908031
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Non-Small Cell Lung Cancer Cells to Gefitinib and Reversal of Epithelial–Mesenchymal Transition by Aloe-Emodin Via PI3K/Akt/TWIS1 Signal Blockage

Abstract: ObjectiveTo explore the impacts of AE (aloe-emodin) in gefitinib-resistant NSCLC (non-small cell lung cancer) cells and the corresponding mechanism.MethodsPC9 and PC9-GR cells were cultured and treated by gefitinib, AE, or the combination of the two drugs. Then, viability, apoptosis, migration and invasion of cells were investigated using CCK-8, TUNEL, wound healing assay, and transwell assay, respectively. Female BALB/c nude mice were employed for the establishment of xenograft tumor models to examine the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Aloe‐emodin and rhein , which are also found in rhubarb, were demonstrated in the same study by Way et al to reduce EMT and tumor sphere‐formation in FaDu cells 156 . More recent studies have further shown that aloe‐emodin decreases Twist1 protein and mRNA levels in gefitinib resistant NSCLC cells, likely at least in part though the PI3K/Akt pathway, 161 while rhein prevents renal tubular epithelial cell EMT in renal fibrosis, potentially through reversal of TGF‐β blockage of SirT1, which in turn, inhibits Stat3 and subsequently Twist1 162 …”
Section: Twist1mentioning
confidence: 72%
“…Aloe‐emodin and rhein , which are also found in rhubarb, were demonstrated in the same study by Way et al to reduce EMT and tumor sphere‐formation in FaDu cells 156 . More recent studies have further shown that aloe‐emodin decreases Twist1 protein and mRNA levels in gefitinib resistant NSCLC cells, likely at least in part though the PI3K/Akt pathway, 161 while rhein prevents renal tubular epithelial cell EMT in renal fibrosis, potentially through reversal of TGF‐β blockage of SirT1, which in turn, inhibits Stat3 and subsequently Twist1 162 …”
Section: Twist1mentioning
confidence: 72%
“…Carboplatin treatment was also associated with increased ERK activity, which was prevented by COM33 administration. Furthermore, Peng and colleagues found that aloe emodin could reverse acquired gefitinib resistance in NSCLC as part of their study referenced earlier [116]. Nisin, a preservative produced as part of bacterial fermentation, was able to reduce TWIST1 expression in liver cancer, following the binding of nisin to the frizzled receptor FZD7 [131].…”
Section: Drugs Targeting Emtmentioning
confidence: 88%
“…The same study found that the expression of LMNA reversed EMT via the inhibition of MAPK signals and preserved drug sensitivity. Peng et al derived a gefitinib-resistant cell line and found that compared to the parent, the resistant line exhibited mesenchymal markers, such as TWIST1, vimentin, and Slug, as well as increased PI3K/Akt activity [116]. These findings echo the involvement of Akt survival signaling in drug resistance discussed at length for the cytotoxic drugs above.…”
Section: Emt and Response To Growth Factor Inhibitionmentioning
confidence: 94%
“…Such Bayesian network evaluations can maximize estimate precision levels (in comparison to the sole and direct scientific data), together with enabling the evaluation of comparative effectiveness for two specific therapies, even when no investigation previously conducted a direct comparative analysis [26]. Furthermore, this review did not include the emerging evidence regarding gefitinib resistance in NSCLC and additional novel therapeutic options that are currently being developed to mitigate such chemotherapeutic resistance issues within clinical cases of EGFR mutation-positive NSCLC, including the possible deployment of long non-coding ribonucleic acid (RNA) and microRNA molecular players to carry out such chemoresistance mitigation effector functions [27][28][29].…”
Section: Gefitinib Effectiveness On Egfr Mutationsmentioning
confidence: 99%